Prediksi Debit Aliran Sub-DAS Bantimurung Menggunakan Model HEC-HMS - Sitti Zulaeha; Sitti Nur Faridah; Mahmud Achmad; Husnul Mubarak (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2020)
Bantimurung watershed is the resource of irrigation water for the surrounding communities and the last few years the change in the magnitude of the maximum discharge and the minimum discharge fluctuates considerably. This study aimed to predict the flow discharge and investigate the validity of HEC-HMS model (Hydrologic Engineering Center's Hydrologic Modeling System) in predicting the flow discharge in the Bantimurung watershed of Maros Regency. The method used in this study was a quantitative method which included data collection of the research data in the field, such as rainfall data, discharge flow rate, soil texture and land use as well as the characteristics of Bantimurung watershed. Data analysis was done using HEC-HMS software. This software performed empirical simulation using rainfall, land slope, land use, soil physical characteristics and generate predicted discharge flow rate. The HEC-HMS model was calibrated using data from Public Work (PU) which were collected in 2006. The calibrated model was then validated using 2014 data. The calibration and validation results indicated that the predicted data were in good agreement with measured data R2 and NSE value of 0,546 and 0,595 respectively from the calibration process and 0,512 and 0,490 from the validation process. These results suggest that the HEC-HMS model can predict the measured discharge flow rate adequately